ASURANSI SYARIAH SEBAGAI BENTUK PERLINDUNGAN - Sumar’in Sumar’in (Prosiding Seminar Nasional Indonesia, 2023)
Sharia insurance was born on the basis of the concept of an insurance agreement (at- ta'min contract) which is a new type of contract that never existed at the beginning of the development of Islamic fiqh. The need for insurance services is increasingly felt by both individuals and the business world in Indonesia. Insurance is a financial means in household life, both in dealing with basic risks or in dealing with risks to assets owned. Insurance in Islam is part of the principle of life based on monotheism. Every human being realizes that in fact each person does not have any power when a disaster comes from Allah SWT, whether it is in the form of an accident, death, or other disaster beyond our predictions as humans.